The Impact of Knee Pain on the Quality of Life and Physical Activity in Middle Age Women (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Approximately 25% of individuals over the age of 50 experience knee pain, with over 50% of these individuals reporting moderate to severe pain consistently. The World Health Organization defines quality of life as a "state of complete physical, mental, and social well-being, and not merely the absence of disease and infirmity."Objective: To examine the impact of knee pain in middle age women on daily physical activity and their quality of life.Materials and methods: A total of 70 women aged between 45 and 65 years participated in the study. Synovial fluid was collected from 40 of the participants and cultured to detect bacterial growth, tested for presence of crystals and white blood cell count. All participants completed a questionnaire specifically designed for this study. Physical performance was tested using the Health-ABC battery. The quality of life was assessed using the EQ-5D, developed by the European Quality of Life Group.Results: The leading cause of knee pain was osteoarthritis, affecting 65.7% of participants. Rheumatoid arthritis and gout arthritis were less common. All the synovial fluid cultures showed no growth of bacteria. While 30% of the synovial fluid showed presence of monosodium urate crystals. The white blood cell count was higher in patients with rheumatoid arthritis (Median=7100 cell/mm3) in compare to the patients with osteoarthritis and gout arthritis. The findings of the present study revealed that the severity of arthritis pain varies in its intensity from moderate to severe and more than half of studied women had a severe pain intensity. Patients scored very low on the quality of life subscale.Conclusion: The intensity of pain is greatest during activities that require standing, walking, crouching, or joint flexion.